2020
DOI: 10.3390/pr8121551
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Substrate Limitation and Light Acclimation in Cultures of the Microalgae Scenedesmus obliquus—Parameter Identification and Model Predictive Control

Abstract: In this study, the parameters of a dynamic model of cultures of the microalgae Scenedesmus obliquus are estimated from datasets collected in batch photobioreactors operated with various initial conditions and light illumination conditions. Measurements of biomass, nitrogen quota, bulk substrate concentration, as well as chlorophyll concentration are achieved, which allow the determination of parameters with satisfactory confidence intervals and model cross-validation against independent data. The dynamic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Numerous microalgae models have been developed based on this idea. 8,9,30,31 These investigations have shown that accurate models can be conceived by incorporating several growth-limiting factors into Eqn (1), such as distinct media compositions (also termed substrates), new photo-acclimation expressions, or even internal lipid content. However, despite having a complex model that accurately describes the growth in the PBR, these numerical expressions are always subject to parametric uncertainties, unknown dynamics, environmental changes, and cell adaptations.…”
Section: Continuous Microalgae Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous microalgae models have been developed based on this idea. 8,9,30,31 These investigations have shown that accurate models can be conceived by incorporating several growth-limiting factors into Eqn (1), such as distinct media compositions (also termed substrates), new photo-acclimation expressions, or even internal lipid content. However, despite having a complex model that accurately describes the growth in the PBR, these numerical expressions are always subject to parametric uncertainties, unknown dynamics, environmental changes, and cell adaptations.…”
Section: Continuous Microalgae Modelsmentioning
confidence: 99%
“…From Eqn (1), new states can be added to the system of equations to include new variables, such as the internal cell quota, and accurately describe the microalga's growth. Numerous microalgae models have been developed based on this idea 8,9,30,31 . These investigations have shown that accurate models can be conceived by incorporating several growth‐limiting factors into Eqn (1), such as distinct media compositions (also termed substrates), new photo‐acclimation expressions, or even internal lipid content.…”
Section: Continuous Microalgae Modelsmentioning
confidence: 99%
“…By incorporating the mathematical description of photoacclimation and applying appropriate kinetic expressions for the nitrogen intake rate (ρ) and the specific growth rate (µ), the Droop's mass balance differential equation for biomass x, substrate y, and intracellular nitrogen quota z are determined for an assumed perfectly mixed PBR [56,58,59]; the model nomenclature is described in detail in Table 1.…”
Section: Dynamic Photoacclimation Modelmentioning
confidence: 99%
“…In this equation, D is the dilution rate (the ratio of the flow rate of the influent over the volume of the photobioreactor), and Dy in is the influent nutrient concentration of nitrate in the influent. The respiration rate is expressed by R. The uptake rate assumed in this model corresponds to that defined by the Michaelis-Menten law, and the specific growth rate is expressed in terms of the intracellular nitrogen quota (z) [54][55][56]58,60]. In order to calculate the remaining parameters of the model, the expressions in ( 2)-( 11) are used.…”
Section: Dynamic Photoacclimation Modelmentioning
confidence: 99%
“…The study [7] is devoted to parameter estimation of a dynamic model for cultures of the microalgae Scenedesmus obliquus using datasets collected in batch photo-bioreactors operated with various initial and light illumination conditions. Measurements of biomass, intracellular substrate quota, extracellular substrate, and chlorophyll concentrations are collected from nine batch experiments differing by their initial and light exposition conditions.…”
mentioning
confidence: 99%